A network integration oriented model to evaluate new wind power generation projects - Cobuloğlu, Halil İbrahim. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
For a continuous and sustainable economic growth, energy is one of the most important necessities that has to be supplied properly. Not only for a continuous economic growth but also for a better environment, renewable energy sources gain more and more importance, and new investments are made to supply electrical energy from those sources. Turkey, as one of the largest and continuously growing economies in the world, wants to increase the share of renewable energy sources in its overall energy supply. For this purpose recently, legislation featuring new incentives and support for new and existing renewable energy projects has frequently been on the agenda of the Turkish parliament. This thesis is about a specific problem originating from the expected rapid expansion of renewable energy generation projects. It is aimed to provide two basic optimization solutions, focusing on reduction in connection cost and increase in energy delivery and installed capacity, to evaluate the most suitable new wind power generation projects. In order to provide an evaluation of new wind power generation projects, a couple of optimization models have been developed to identify the wind power projects to be invested in especially regarding their connection points, and connection voltage levels. First, necessary information is explained and description of data is provided while establishing the model constraints. Then, data set is introduced to be used in the models for sensitivity analysis. Models are coded in C++ and solved by using the Cplex optimization solver. The results of a series of scenarios are obtained and analyzed, and future research opportunities are explained with addition of some comments on the results.
Keywords: Wind power plants.; Wind energy conversion systems.; Wind turbines.